"It's like this Myth of the Supernegro": resisting narratives of damage and struggle in the neoliberal educational policy context. Issue 6 (2nd November 2017) - Baldridge, Bianca J.
Abstract: As pathologizing, racialized, and patriarchal rhetoric undergirds neoliberal education reform, deficit narratives characterize the education of Black youth. Such narratives present deep challenges for educational policy and community-based educational spaces. This article explores the ways in which community-based educators resist narratives of damage and struggle in their own personal and professional narratives in order to prevent the cycle of deficit-oriented discourse that follow Black youth through myriad educational spaces. By situating the narratives of community-based educators within a broader policy context shaped by race, class, and gender, this article illustrates the challenges that arise for community-based educators that seek to frame Black youth beyond deficit narratives and who avoid framing themselves as heroes and saviors of Black youth.